Interweaving Voices: An Interdisciplinary View. A Methodological Proposal Based on Literacy - Badilla Zamora, Isabel (2022)
This article systematizes the experience of the interdisciplinary meetings from the Literacy Integrated Project. A Look from Literacy to Build Inclusive Reading Environments, from Early Childhood to Prolongevity, as a strategy to move forward with an alternative methodological proposal to approach reading and writing processes from a literacy perspective. The means to collect participants’ views included discussions with scholars from various fields and schools from UNA, as well as written records, recordings, transcripts, matrixes, and analyses of these discussions. As a result, several philosophical and methodological principles and paths emerged to move towards a broad, inclusive approach to reading and writing processes in line with literacy through the five systematization steps proposed by lecturer Oscar Jara.